Decision making on consistent customer centric inventory model with quality sustenance and smart warehouse management cost parameters - Miriam, Renee; Martin, Nivetha; Rezaei, Akbar (Decision Making: Applications in Management and Engineering, 2023)
Customer acquaintance and the quality of the products decide the survival span of all the business sectors. Every production firm attempts to manufacture novel products with attractive and compatible features to satisfy the demands of different types of customers, especially with a special preference for the consistent kind of customers. A decision-making inventory model compassing the initiatives taken by the production firm for consistent customers is developed with the inclusion of costs associated with quality conservation and warehouse management. The reliability of the model is validated with numerical examples and inferences on parametric variations are made by comparing the results employing MATLAB software. The proposed model shall be further discussed in a fuzzy environment